1996
DOI: 10.3109/10731199609118885
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Vacuole Formation Following a Bolus Infusion of Peg-Hemoglobin in the Rat

Abstract: This study was designed to assess the morphological effects of a bolus infusion of PEG-hemoglobin on the heart, lung, liver, spleen and kidney of laboratory rats. Of particular interest was the determination of PEG-hemoglobin's potential to form vacuoles in the tissues and whether these were transitory and article specific. One hundred ten female Sprague-Dawley rats were used in this study. The first experiment determined whether vacuole formation was test article specific by infusing either stroma-free bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Vacuole formation has also been reported for haemoglobin (Hb) and bovine serum albumin (BSA), both conjugated to a 5 kDa PEG . Rats treated with a single i.v.…”
Section: Cell Vacuolation After Administration Of Unconjugated Peg Anmentioning
confidence: 92%
“…Vacuole formation has also been reported for haemoglobin (Hb) and bovine serum albumin (BSA), both conjugated to a 5 kDa PEG . Rats treated with a single i.v.…”
Section: Cell Vacuolation After Administration Of Unconjugated Peg Anmentioning
confidence: 92%
“…PEG itself has been approved by the FDA for use in food and cosmetics, and itself is considered essentially nontoxic 16, 17. Uptake of PEGylated drugs into Kuppfer cells in the liver has also been reported,12 and while some reports indicate that such intracellular uptake of PEGylated molecules can lead to vacuolization, no toxic consequences of this phenomenon have been observed 18–20. Researchers have attempted to capitalize on this postulated cellular uptake property of PEG by using it to enhance uptake of enzymes such as catalase and superoxide dismutase into cells and deliver to their site of action 21.…”
Section: Pharmacological Properties Of Pegylated Drugsmentioning
confidence: 99%
“…Several studies have shown that PEGylated proteins induced vacuole formation in organs including liver, kidneys and spleen [7-11]. One should keep in mind however, that in the majority of these studies, the PEGylated protein is bovine hemoglobin (bHb), which is known to be absorbed by the liver and spleen [11]. In addition, the various studies investigating this issue have reported some contradictory findings.…”
Section: Introductionmentioning
confidence: 99%